LALINET The First Latin American-Born Regional Atmospheric Observational Network - Antuna-Marrero, JC (2017)
Sustained and coordinated efforts of lidar teams in Latin America at the beginning of the twenty-first century have built the Latin American Lidar Network (LALINET), the only observational network in Latin America created by the agreement and commitment of Latin American scientists. They worked with limited funding but an abundance of enthusiasm and commitment toward their joint goal. Before LALINET, there were a few pioneering lidar stations operating in Latin America, described briefly here. Biannual Latin American lidar workshops, held from 2001 to the present, supported both the development of the regional lidar community and LALINET. At those meetings, lidar researchers from Latin America met to conduct regular scientific and technical exchanges among themselves and with experts from the rest of the world. Regional and international scientific cooperation has played an important role in the development of both the individual teams and the network. The current LALINET status and activities are described, emphasizing the processes of standardization of the measurements, methodologies, calibration protocols, and retrieval algorithms. Failures and successes achieved in the buildup of LALINET are presented. In addition, the first LALINET joint measurement campaign and a set of aerosol extinction profile measurements obtained from the aerosol plume produced by the Calbuco volcano eruption on 22 April 2015 are described and discussed.